2018
DOI: 10.21053/ceo.2018.00115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adenotonsillectomy on Attention in Korean Children With Sleep-Disordered Breathing

Abstract: Objectives Pediatric sleep-disordered breathing (SDB) is a common debilitating disorder that can adversely affect the attention and academic performance of school-age children. Unfortunately, only a few studies have examined the effect of SDB treatment on attention in pediatric populations. Therefore, the aim of this study was to prospectively investigate the effect of SDB treatment on attention in children.Methods This study consecutively enrolled SDB children with adenotonsillar hypertrophy. All subjects und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…As has been evidenced previously, the treatment of SDB not only improves children's breathing quality during sleep, but also effectively decreases aggressive, inattentive, and hyperactive behaviors. 34,35 Therefore, if children have both SDB and ADHD symptoms, treatment of SDB may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…As has been evidenced previously, the treatment of SDB not only improves children's breathing quality during sleep, but also effectively decreases aggressive, inattentive, and hyperactive behaviors. 34,35 Therefore, if children have both SDB and ADHD symptoms, treatment of SDB may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Adenotonsillectomy is currently one of the most common surgical procedures performed in children. [ 10 ] However, postoperative pain and PONV, followed by poor oral intake, dehydration, prolonged hospitalization, and postoperative hemorrhage still remain problems. [ 11 14 ] In addition, these problems lead to poor patient satisfaction, impair recovery, and increase health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to allergens is crucially important in the induction of sensitization and the development of atopic diseases, which often influence quality of life in terms of sleep, school, work, and social life [21][22][23]. Several studies have reported that the global prevalence of atopic diseases has risen significantly over the last 2 decades [24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%